Study of industrial accidents as preventive action at a construction company - Atencio, Roberto (2014)
Today, in Peru, the occurrence of an accident at construction companies, strongly affects the stability of a company and the achievement of future work projects, major construction companies, require high standards of security for their contractors. The aim of this study was to create a working protocol as preventive action accidents in a construction company. Also, determine the prevalence of accidents according to characteristics of the accident. A study was conducted non-experimental, descriptive and transversal. Detailed information was obtained from each worker who had accidents in two projects of a construction company during the years 2010 to 2011.